A Scoping Review of Predictors of Community Integration Following Traumatic Brain Injury: A Search for Meaningful Associations. Issue 4 (July 2019) - Kersey, Jessica; Terhorst, Lauren; Wu, Chao-Yi; Skidmore, Elizabeth
Abstract : Objective: The purpose of this scoping review was to identify predictors of community integration for adults with traumatic brain injury. Data Sources: We searched the PubMed and PsycINFO databases and reviewed references of included studies. We selected studies exploring multiple components of community integration, including instrumental activities of daily living, leisure activities, and social activities. A total of 53 studies were included. Data Extraction: We extracted data on sample size and sample characteristics (stage of injury and recovery, severity) and examined predictor variables, outcome measures for community integration, and significant findings, reported as correlations. Data Synthesis: We found that the predictors of community integration fell into 4 categories: demographics, injury characteristics, disability and impairments, and environmental factors. There was large variability in reported relationships for demographics ( r = 0.01-0.43), injury characteristics ( r = 0.01-0.58), disability/functional impairments ( r = 0.003-0.98) and environmental factors ( r = 0.11-0.58). Cognition, disability, mobility/physical functioning, mood, social support, and length of posttraumatic amnesia had the strongest relationships with community integration outcomes. Conclusions: Strategies for the management of cognitive, physical, and emotional functioning, and building and training a strong support system, may facilitate community integration outcomes. Additional work is warranted to further explore the discrepancies found among studies. Abstract : Supplemental Digital Content is Available in the Text.